Strengthening Islamic Education for People with Epilepsy (ODE) Patients with Psychological Approaches in Lamongan: Penguatan Pendidikan Islam Pada Pasien Orang Dengan Epilepsi (ODE) Dengan Pendekatan Psikologis Di Lamongan - Hadi , Muhammad Fazlurrahman; Khoirunisaa, Ismaidah (Halaqa: Islamic Education Journal, 2023)
One of the functions of Islamic education in the family is to pass on and develop Islamic values to family members considering that religion is a psychological need that must be fulfilled and often physical illnesses start from poor psychological conditions. Psychological factors that trigger epileptic seizures in ODE patients, lack of family support and negative societal stigma towards patients are the background for this research so that psychological monitoring is needed for ODE patients through strengthening Islamic values in the family to reduce epileptic attacks and improve health development and quality of life for ODE . The aim of this research is to comparatively analyze and describe the health development profile of ODE patients through three treatment models, namely (1) medical treatment accompanied by strengthening Islamic values in the family, (2) medical treatment without strengthening Islamic values in the family, (2) medical treatment without strengthening Islamic values in the family, (3) strengthening Islamic values in non- medical families So it is known which treatment model best supports the healing progress of ODE patients. This research uses descriptive qualitative approach with the type of case study on ODE patients in Laren sub-district, Lamongan district . The data collection techniques are through observation and documentation at the Laren Community Health Center, village hall, village midwife's house and the patient's residence as well as in depth interviews involving 1 health worker, 5 ODE patients and 4 patient families as research objects as well as 1 village head, 5 village governments and 2 village midwives as informants . Next, the data was analyzed through the data reduction stage, data presentation and drawing conclusions. The results of the study showed that ODE patients with medical treatment accompanied by strengthening Islamic values in the family consisted of patients with mild, moderate and serious types of epilepsy with the intensity of recurrence rarely showing very good health progress, whereas patients with medical treatment without strengthening Islamic values in the family. The family consists of patients with serious types of epilepsy with the intensity of recurrence often showing poor health development and patients with moderate types of epilepsy with recurrence intensity rarely showing good health development and there are no patients who are only given reinforcement of Islamic values in the family without medical treatment . The implications of the research results, theoretically, show the suitability of Al-Balkhi's psychological theory regarding the correlation of physical and mental health, the development of a model for treating mental disorders based on Islamic values which has a significant impact on various levels of severity of physical illness and strengthening Islamic values is directly proportional to prevention. or reduction of psychological disorders. Practically speaking, this research is a problem solving for ODE patients, patient families, public health institutions, village government and village midwives in the patient's area of residence as well as changing the negative stigma of society towards ODE patients.